Twinless [videorecording (Blu-Ray)] - Chŏng, Chae-il, 1982- (Lionsgate, 2026)
"This thought-provoking and at times disarmingly comic film from writer-director James Sweeney explores themes of friendship, love, and life-altering loss. Two men, Roman (Dylan O'Brien) and Dennis (James Sweeney), meet and form an unlikely bond in a twin support group as they search for solace and identity without their other halves. But when Roman meets Dennis's ebullient colleague, Marcie (Aisling Franciosi), things begin to fall apart as each man harbors secrets that could unravel everything."--Container.